Acceptance of group awareness information from varying sources: on competence and gender - Freund, Laura-Jane; Schnaubert, Lenka; Bodemer, Daniel (Frontiers in Education, 2025)
Group awareness tools are used for collecting, transforming, and presenting information about potential learning partners. Their use may be influenced by the credibility a learner assigns to the source of such information. In a 2x2x2 mixed design study (N = 152), we investigate how source type (teacher assessment/self-assessment) interacts with gender of a potential learning partner (male/female) and competence level (high/low) of a potential learning partner. In line with existing research, we found that information from external sources is perceived more credible than information from internal sources with teacher assessments being more credible compared to self-assessments. In addition, the type of source interacts with both the gender and the competence level of learning partners when judging the credibility of a source. As the acceptance of information plays a key role in group awareness, it is worth considering the identified effects in future research, especially when focusing on possible designs of such tools.